SISTEM PENGOLAHAN BAHAN PUSTAKA - Ramadhani, Desy Nuraulia; Sahidi, Sahidi (Universitas Tanjungpura, 2023)
This article is entitled The Library Materials Processing System at Public Elementary School 34 Pontianak Kota. Every process of processing library materials should be in accordance with the procedures already given, and in the library studied it does not perform any of the procedures for processing library materials. The method used is a qualitative method of describing fact information in the field. Data collection techniques through interviews, observation of documentation techniques. The number of informants as a source of data in this study were two informants who served in the processing department. The resultsof this study show that the SDN 34 Library Materials Processing System of Pontianak City through inventory activities, book classification, book data input (Bibliographic data input), Lebeling, book completeness. The book's completeness consists of a book card and a bookcase, followed by a shelf. However, the Library of Elementary School 34 of Pontianak Kota did not perform the spelling. Processing in this library is still manual and electronic. The challenge faced was the lack of human resources in managing Library materials, so the processing of materials was slow